(untitled) (International Journal of Child Health and Nutrition, 2020)
Child malnutrition is a public health problem in developing countries, and dietary diversity is one of the important determinants of undernutrition. Different nutrients are obtained from different food groups and to meet the requirement of recommended Dietary Allowances entitled as Dietary Diversity. The current review revealed that the nutrition status of children is directly related to the food groups consumed. Food diversity depends on many factors such as Socio-economic Status, education level, sex, and age of the subjects. The food group consumed and food items taken from each group were low in the low Socio-Economic Status (SES) subjects, rural areas, females, and less educated families, resulting in malnutrition among children of various countries. Low level of Dietary Diversity can be the reason for undernutrition in children worldwide, especially in developing countries. Many studies thus supported that Dietary Diversity and Food Variety can provide nutritional adequacy.